Pengaruh Modal Kerja, Resiko Bisnis, dan Ukuran Perusahaan terhadap Profitabilitas pada Perusahaan Manufaktur Sektor Makanan dan Minuman di BEI Periode 2017-2021 - Dina Nur Fatmah; Gendro Wiyono; Alfiatul Maulida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the effect of working capital, business risk and company size on profitabuluty. In this study the variable profitability is measured using return on assets (ROA). This type of research is quantitative and also uses a purposive sampling technique, meaning that the sample selected is in accordance with predetermined criteria. The population of this study are food and beverage industry companies listed on the indonesia stock exchange from 2017 to 2021 with a total of 32 companies. The sample of this research is 20 companies seleced according tp presetermined ceritera. Therefore the methode used uses multiple linear regression analysis because of the number of independen variables in this study there are three variables. The results of this study indicate that turnover capital does not affect profitability, because companies use and control turnover capital in companies that are carried out effectively and effectively, and this business risk does not effect profitability. This is also due to the instability of cosst and company profit. Company size affects profitability, this is because company size is taken into account on the balance sheet, it is easier to get company profits. Keyword : working capital, business risk, firm size, profitability